Does an education major matter for teaching? The relationship between teachers' degree and student achievement - Marcelo Drouet; Gregory Elacqua; Luana Marotta; Leonardo Rosa (Inter-American Development Bank (IDB), 2022)
It is unclear whether teachers with a degree in education are more effective than those who are not trained in an education-related field. To further examine this issue, we analyze the relationship between teachers' college major and student achievement by using unique data from Ecuador, which, for a period of time, allowed any graduate, regardless of their major, to apply for a teaching position in the country's centralized selection process. Results from all specifications indicate a non-significant relationship between degree type and student achievement, suggesting that teachers with and without an education degree are equally effective. We also found that teachers' content-related and pedagogical knowledge do not seem to mediate the relationship between having an education degree and student learning. Finally, we observe no heterogeneous effects across different student demographic and socioeconomic characteristics. Examining these claims empirically is crucial for ensuring that greater flexibility in teacher recruitment does not have negative effects on the quality of the education workforce.
Keywords: I20; I21; I28; 330; Teacher quality; teacher credentials; teacher degree requirements; student achievement